Spatiotemporal variations of below-ground monoterpene concentrations in an upland black spruce stand in interior Alaska - Morishita, Tomoaki; Miyama, Takafumi; Noguchi, Kyotaro; Matsuura, Yojiro; Kim, Yongwon (Polar Science, 2019)
Monoterpenes play important roles in atmospheric chemistry and g lobal warming, and their sources and sinks have been investigated. However, there is no information about monoterpene concentrations in black spruce (Picea mariana) forest soil. Here, we investigated seasonal and spatial variations of monoterpene concentrations in soil of an upland black spruce stand in interior Alaska. The site comprised three plots with different tree biomasses, organic layer depths, and vegetation types (mosses and lichens). At each plot, monoterpene concentrations in air in the atmosphere, the soil, and the organic layer under various vegetation types (including leaf litter) were determined. Nine monoterpenes were identified: α-pinene, camphene, β-pinene, 3-carene, sabinene, myrcene, p-cymene, limonene, and β-phellandrene. The total monoterpene concentration in the atmosphere was <0.01 mg m−3, whereas the total concentration in the organic layer sometimes exceeded 1.0 mg m−3. The total monoterpene concentration in the organic layer was lower in the fall than in the spring and summer, and the concentrations differed among the plots, perhaps because of differences in tree biomass and vegetation. The most abundant monoterpene in the organic layer was α-pinene, accounting for ∼50% of the total monoterpenes; and camphene emission may a unique feature of black spruce forest soils. journal article